Familiar and comfortable vs. unfamiliar and demanding – Students' discourses on teachers’ responsibility and leadership in Finnish early childhood education - Kahila, Sanni; Heikka, Johanna; Sajaniemi, Nina (Teaching and teacher education, 2024)
This study explored discourses on teachers' responsibility and leadership in Finnish early childhood education. Semi-structured focus group interviews (n = 17) involved 41 early childhood education students, including pre-service teachers (n = 20), social pedagogues (n = 9), and childcarers (n = 12). Two contrasting main discourses were identified: “familiar and comfortable, equally shared responsibility” and “unfamiliar and demanding, differentiated responsibility and leadership”. The findings indicate ambiguity about teachers’ responsibility and leadership, avoidance of the term leadership, concerns about occupational well-being, and uncertainty about leading teamwork. The study provides insights for encouraging teachers' professional development towards increased leadership responsibilities. •Students produced contrasting discourses on teachers' responsibility and leadership.•Discourses reflect the lack of clarity concerning the link between teachers' responsibility and leadership.•The term leadership is avoided when referring to teachers' responsibilities.•Regarding future working life, discourses show students' doubts about leading and improving teamwork.•Worries about professionals' occupational well-being were highlighted in the students' discourses.